Holding back the tiger: Successful control program protects Australia from Aedes albopictus expansion - Muzari, Mutizwa Odwell; Devine, Gregor; Davis, Joseph; Crunkhorn, Bruce; van den Hurk, Andrew; Whelan, Peter; Russell, Richard; Walker, James; Horne, Peter; Ehlers, Gerhard; Ritchie, Scott (PLOS Neglected Tropical Diseases, 2017)
Background The Asian tiger mosquito, Aedes albopictus, is an important vector of dengue, chikungunya and Zika viruses and is a highly invasive and aggressive biter. Established populations of this species were first recognised in Australia in 2005 when they were discovered on islands in the Torres Strait, between mainland Australia and Papua New Guinea. A control program was implemented with the original goal of eliminating Ae. albopictus from the Torres Strait. We describe the evolution of management strategies that provide a template for Ae. albopictus control that can be adopted elsewhere. Methodology / Principal findings The control strategy implemented between 2005 and 2008 targeted larval habitats using source reduction, insect-growth regulator and pyrethroid insecticide to control larvae and adults in the containers. However, the infrequency of insecticide reapplication, the continual accumulation and replacement of containers, and imminent re-introduction of mosquitoes through people’s movement from elsewhere compromised the program. Consequently, in 2009 the objective of the program changed from elimination to quarantine, with the goal of preventing Ae albopictus from infesting Thursday and Horn islands, which are the transport hubs connecting the Torres Strait to mainland Australia. However, larval control strategies did not prevent the species establishing on these islands in 2010. Thereafter, an additional strategy adopted by the quarantine program in early 2011 was harborage spraying, whereby the vegetated, well shaded resting sites of adult Ae. albopictus were treated with a residual pyrethroid insecticide. Inclusion of this additional measure led to a 97% decline in Ae. albopictus numbers within two years. In addition, the frequency of container treatment was increased to five weeks between treatments, compared to an average of 8 weeks that occurred in the earlier iterations of the program. By 2015 and 2016, Ae. albopictus populations on the two islands were undetectable in 70–90% of surveys conducted. Importantly, a comprehensive surveillance network in selected strategic areas has not identified established populations of this species on the Australian mainland. Conclusions / Significance The program has successfully reduced Ae. albopictus populations on Thursday Island and Horn Island to levels where it is undetectable in up to 90% of surveys, and has largely removed the risk of mainland establishment via that route. The vector management strategies adopted in the later years of the program have been demonstrably successful and provide a practical management framework for dengue, chikungunya or Zika virus outbreaks vectored by Ae. albopictus. As of June 2016, Ae. albopictus had not established on the Australian mainland and this program has likely contributed significantly to this outcome.